2017
DOI: 10.1186/s12933-017-0576-9
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical carotid atherosclerosis in patients with latent autoimmune diabetes in adults (LADA), type 2 diabetes and classical type 1 diabetes

Abstract: BackgroundLADA is probably the most prevalent form of autoimmune diabetes. Nevertheless, there are few data about cardiovascular disease in this group of patients. The aim of this study was to investigate the frequency of carotid atherosclerotic plaques in patients with LADA as compared with patients with classic type 1 diabetes and type 2 diabetes.MethodsPatients with LADA were matched for age and gender in different proportions to patients with type 2 diabetes, and classic type 1 diabetes. None of the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…Another cross-sectional study showed that LADA patients had a higher prevalence of carotid atherosclerosis than age-matched T2D patients. 19 These results were in contrast with findings from the prospective population-based HUNT2 study, that showed all-cause mortality and CV mortality to be equal in LADA and T2D patients. 20 Unlike the UKPDS, however, the HUNT2 study did not evaluate nonfatal events, had a shorter mean follow-up period (9.1 years among patients with diabetes) and the diagnosis of LADA was based on measurement of only one AAb.…”
Section: Effect Of Assigned Glycaemic Strategy On CV Outcomes By Lamentioning
confidence: 57%
See 1 more Smart Citation
“…Another cross-sectional study showed that LADA patients had a higher prevalence of carotid atherosclerosis than age-matched T2D patients. 19 These results were in contrast with findings from the prospective population-based HUNT2 study, that showed all-cause mortality and CV mortality to be equal in LADA and T2D patients. 20 Unlike the UKPDS, however, the HUNT2 study did not evaluate nonfatal events, had a shorter mean follow-up period (9.1 years among patients with diabetes) and the diagnosis of LADA was based on measurement of only one AAb.…”
Section: Effect Of Assigned Glycaemic Strategy On CV Outcomes By Lamentioning
confidence: 57%
“…On the contrary, in a recent cohort study LADA seemed to be associated with lower short‐term risk of CV events and mortality, even though patients with insulin‐dependent diabetes were not considered as possibly affected by LADA. Another cross‐sectional study showed that LADA patients had a higher prevalence of carotid atherosclerosis than age‐matched T2D patients . These results were in contrast with findings from the prospective population‐based HUNT2 study, that showed all‐cause mortality and CV mortality to be equal in LADA and T2D patients .…”
Section: Discussionmentioning
confidence: 90%
“…In both cases, well-known cardiovascular risk factors and, more importantly, advanced stages of DR were independently associated with subclinical atherosclerosis. Interestingly, in a recent study, we have reported that the frequency of preclinical carotid atherosclerosis in patients with latent autoimmune diabetes of the adults (LADA) is similar, or even greater in those with longer disease duration, to subjects of similar age with classic type 1 diabetes and type 2 diabetes [ 31 ]. In LADA, preclinical carotid atherosclerosis was also associated with classical risk factors like hypertension and tobacco exposure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Limited data suggest that cardiovascular comorbidity and mortality in such individuals are comparable to that of other people with type 2 diabetes. [2][3][4][5][6] However, the effect of different treatment regimens on clinical outcomes in the subgroup that are anti-GAD positive remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%